Edukasi Pencegahan Dermatitis Paederus Pada Santri - Dwi Suharyanta (Humanism: Journal of Community Empowerment (HJCE), 2023)
Dermatitis is a form of inflammation of the epidermis and dermis in response to exogenous or endogenous factors, it causes of clinical abnormalities in the form of polymorphic efflorescence (erythema, edema, papules, vesicles, scales, lichenification) and complaints of itching. The location of this service is in the Islamic boarding school in Bantul district. And they who have complaints of Paederus dermatitis caused by Paederus insects and it can be called tomcat. Some students complained about this situation. Meanwhile, from the results of the interviews conducted, data was obtained that many students did not know how to manage and prevent these insect attacks, so it is necessary to educate students to prevent this. The purpose of the activity is to increase the knowledge of Islamic boarding school managers and students in Prevention of Paederus dermatitis. The activity was carried out using the lecture method, making educational media and installing educational media (posters). As for the results of educational activities prevention of paederus dermatitis carried out on students has been carried out with three activities namely socialization and education on prevention of paederus dermatitis, making educational media (paederus dermatitis prevention posters), and installation of educational media and obtained differences in the knowledge of Islamic boarding school students. Besides that, the activities carried out are going well, educational media in the form of posters can be installed at several points as needed.